2022
DOI: 10.1021/acsami.2c02373
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of All-Inorganic Perovskite Solar Cells by Lead–Cerium Bimetal Strategy

Abstract: Owing to the instability of organic materials, an inorganic perovskite solar cell (PSC) attracts much attention in recent years. However, the instability of phase and overmuch traps lead to the inferior performance of inorganic perovskite solar cell, a high performance inorganic PSC is desirable. The element of cerium possesses a suitable chemical and physcial properties to substitute lead. We utilize cerium to partially substitute lead, a lead–cerium (Pb–Ce) bimetal based inorganic PSC is successfully achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…All-inorganic cesium lead halide (CsPbX 3 , X = I, Br) perovskites have attracted much attention because of their superior thermal stability over their organic–inorganic hybrid counterparts, according to both experimental and theoretical results. Among the CsPbX 3 perovskite materials, the mixed halide CsPbI 2 Br is considered the most promising light absorber due to the trade-off between stability and efficiency. CsPbI 2 Br has excellent thermal/light soaking stability and a suitable band gap of ≈1.90 eV, which exhibits promising application potential in the front cell of tandem solar cells. , In recent years, the performance of CsPbI 2 Br perovskite solar cells (PSCs) has been rapidly improved through some innovations, such as modulating the crystallization process, optimizing composition, , and modifying the interface. , Yang et al reported a low-dimensional intermediate-assisted growth (LDIAG) method to control both nucleation and growth kinetics by introducing imidazole halide (IMX: IMI and IMBr) into the precursor solution .…”
Section: Introductionmentioning
confidence: 99%
“…All-inorganic cesium lead halide (CsPbX 3 , X = I, Br) perovskites have attracted much attention because of their superior thermal stability over their organic–inorganic hybrid counterparts, according to both experimental and theoretical results. Among the CsPbX 3 perovskite materials, the mixed halide CsPbI 2 Br is considered the most promising light absorber due to the trade-off between stability and efficiency. CsPbI 2 Br has excellent thermal/light soaking stability and a suitable band gap of ≈1.90 eV, which exhibits promising application potential in the front cell of tandem solar cells. , In recent years, the performance of CsPbI 2 Br perovskite solar cells (PSCs) has been rapidly improved through some innovations, such as modulating the crystallization process, optimizing composition, , and modifying the interface. , Yang et al reported a low-dimensional intermediate-assisted growth (LDIAG) method to control both nucleation and growth kinetics by introducing imidazole halide (IMX: IMI and IMBr) into the precursor solution .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, perovskite PVs emerge as a potential candidates due to their outstanding solar-to-power conversion efficiency . Many different groups of materials have been studied and applied to the hole transport layer (HTL), electron transport layer (ETL), and perovskite layer to enhance the efficiency and stability of perovskite PVs. Carbon nanotubes (CNTs) have attracted worldwide attention to solve this problem due to their unique structure, outstanding mechanical strength and thermal conductivity, and versatile electronic properties. In addition, they possess the limitless potential for decorated additional functions through chemical modification. Many studies show that the presence of CNTs in perovskite PVs can passivate the defect sites in halide perovskites, preventing charge recombination in the perovskite layer. Incorporating CNTs into PVs as a notable strategy in improving the device’s solar energy harvester capabilities, efficiency, stability, and low cost helps bring perovskite PVs and nanocarbon-based PVs closer to widespread commercialization. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, CeO x has been employed as the electron transport layer or as the substitute of Pb ions to show superior properties in PSCs. [ 19,25a,26 ] Moreover, Ce doping can reduce trap density and retard charge recombination, resulting in a significant improvement in the short‐circuit current ( J SC ) and open‐circuit voltage ( V OC ) of the PSCs. [ 27 ] But there is no report about the balance hole migration with CeO x treated the interface between spiro‐OMeTAD and perovskite.…”
Section: Introductionmentioning
confidence: 99%